Externalizing as a common genetic influence for a broad spectrum of substance use and behavioral conditions: A developmental perspective from the Avon Longitudinal Study of Parents and Children. - Deng, Wei Q.; Belisario, Kyla; Doggett, Amanda; Pigeyre, Marie; Pare, Guillaume; Munafò, Marcus R.; MacKillop, James (Addiction, 2025)
Background and aims: Recent large studies have established the genetic basis of several conceptually linked phenotypes of externalizing. Polygenic risk scores (PRSs) for these constructs are associated with a range of substance use and mental disorder phenotypes but have not been examined with both pharmacological and non‐pharmacological addictive behaviors, or across a developmental window. This study identified biological pathways responsible for observed associations between PRSs and addiction phenotypes. Design, setting, participants: We selected genome‐wide association studies of 22 phenotypes, including substance use, general factors of externalizing and addiction, impulsivity and psychiatric conditions. Using summary statistics, we constructed PRSs in the offspring from the Avon Longitudinal Study of Parents and Children (ALSPAC) (nmax = 4995). Participants were genetically confirmed to be unrelated and of European‐like genetic similarity. Measurements: We examined the associations between PRSs and addiction‐related phenotypes including substance use, gambling, eating behaviors and internet use across different life stages, from adolescence to young adulthood. PRSs were partitioned by biological pathways to examine the common and unique mechanisms underlying the genetics of addiction‐related phenotypes. Findings The PRS of externalizing factor (PRSEXT) showed the strongest association across phenotypes for substance use (minP = 2.6 × 10‐31, adjusted R2 = 0.10–4.72%), gambling (minP = 1.0 × 10‐9, adjusted R2 = 0.18–1.50%), eating behaviors (minP = 8.2 × 10‐4, adjusted R2 = 0.11–0.65%) and internet use (minP = 1.4 × 10‐7, adjusted R2 = 0.17–1.04%). Sensitivity analyses excluding a small subset of ALSPAC participants who also contributed to the externalizing summary statistics, yielded consistent association effect sizes (R2 = 0.98), suggesting minimal bias. The results also revealed several time‐varying associations between several PRSs and addiction phenotypes. Notably, the genetic influence of externalizing factor on alcohol and tobacco use was significantly stronger at younger ages. Finally, we identified multiple biological pathways that contribute to the link between addiction‐related phenotypes and PRSEXT, emphasizing the importance of synaptic functions and neuronal plasticity in the context of gambling and substance use. Conclusions: There appears to be genetic evidence implicating externalizing as a common mechanism of substance and behavioral addictive behaviors. These results support the shared genetic liability across substance misuse, problematic gambling and internet use, and demonstrate the potential utility of externalizing traits as a transdiagnostic dimension across diverse forms of psychopathology. Notably, the predictive power of externalizing genetic liability appears developmentally dynamic, supporting the view that externalizing represents a broad, non‐time‐invariant risk factor that may give way to more specific disorder‐related influences over time.